Application Of Principles Of Justice In Mudharabah Agreements In Sharia Financial Institutions - Ayuni Ariya Safitri; Kiki Salastia; Nurul Atiqah; Siti Ruquayah (Penerbit Jurnal Indonesia, 2023)
in the Islamic financial institutions have introduced several financial instruments in lieu of interest instruments. The instrument is an instrument that emphasizes the principle of profit sharing (profit and loss sharing).Profits earned and losses to be borne jointly by the parties to a transaction. Therefore, both parties to a transaction will be mutually keep track of progress and setbacks business carried. Among prisnip for the results of the most prominent and even the most popular is the mudaraba. The purpose of this study is, first, to determine the theoretical concepts of justice and mudharabah and secondly, to determine the application of the principle of fairness in mudharabah in Islamic financial institutions. Data used in this study is a type of primary and secondary data. This study classified the types of Qualitative Research. The results showed that (1) Aristotle distinguishes justice into two kinds: first, distributive justice; and second, the cumulative justice. Mudharabah is a partnership between the owners of the fund or the investor and manager of capital to conduct certain business with profit sharing based on the ratio; (2) the principle of fairness that can be applied in mudharabah on Islamic financial institutions.